Learning from the particular: a study of the individual differences in children's graphic creativity - Palacios Garrido, Alfredo (Pulso. Revista de educación, 2001)
Starting from the premise that diversity is a crucial aspect, the Spanish Organic Act 1990 on the General Organisation of the Education System (LOGSE) advocates a teaching model that considers individual differences in learning.  Building on this, the present article reviews some of the significant contributions in the study of children's drawings towards understanding individual differences in creativity.  The article traces the evolution of ideas from V. Lowenfeld's proposals in the early 1940s to research conducted in the 1990s, highlighting how these contributions not only addressed the intricate issue of differences but also deepened our comprehension of drawing as a means of communication and expression.